(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
In the article the main urban-constructional problems of crisis situations being emerged as a result of natural disasters (particularly earthquakes) are being examined. The main geographical and urban-constructional factors affecting on scales of results of natural disasters are revealed. Activities directed to improvement of urbanconstructional management in crisis situations have been proposed. These may mitigate the results of natural disasters.